200 Gbit/s Photonics-Aided MMW PS-OFDM Signals Transmission at W-Band Enabled by Hybrid Time-Frequency Domain Equalization - Wang, Kaihui; Zhao, Li; Yu, Jianjun (Journal of lightwave technology, 2021)
Millimeter-wave (MMW) transmission has the advantage of larger available bandwidth compared with traditional wireless communications. Compared with the electrical algorithms, photonics-aided MMW signals generation can support a large modulation bandwidth and is regarded as a potential candidate for future RoF link. In this experiment, we demonstrate a W-band (75 GHz ∼ 110 GHz) photonics-aided MMW communication system. To overcome the high-frequency power loss induced by the limited bandwidth of photoelectric devices, we adopt orthogonal frequency division multiplexing (OFDM) signal with hybrid quadrature amplitude modulation (QAM) formats. Moreover, the probabilistic constellation shaping (PCS) technique is used to further improve the system capacity. In the offline digital signal processing (DSP), a time-domain Volterra series based nonlinear equalizer with I/Q multiple input multiple output (MIMO) structure can compensate for the nonlinearity during the fiber and wireless transmission. Finally, a hybrid time-frequency domain least mean square (LMS) equalizer is proposed to eliminate the crosstalk in the adjacent OFDM symbols and subcarriers. With the aid of advanced modulation and hybrid time-frequency domain equalization, 30 Gbaud OFDM MMW signals with hybrid PS-512QAM and PS-128QAM at 92.5 GHz can be successfully transmitted over 1-m wireless link, whose raw transmission rate is 208.4 Gbit/s. It is worth noting that the hybrid time-frequency domain LMS equalizer can increase the maximal AIR to 178.8 Gbit/s.